The environs of Elaia's ancient open harbour – a reconstruction based on microfaunal evidence. (February 2015) - Pint, Anna; Seeliger, Martin; Frenzel, Peter; Feuser, Stefan; Erkul, Ercan; Berndt, Christopher; Klein, Christina; Pirson, Felix; Brückner, Helmut
Abstract: During Hellenistic and Roman times, Elaia, the harbour city of ancient Pergamum, was an important place of trading and traffic. Intense mercantile and military activities are documented by literary sources and archaeological evidences. Geomagnetic and geoelectric investigations detected building structures close to the ancient coastline, which are interpreted as ship sheds. The aim of this study was to reconstruct the coastal evolution, particularly with regard to harbour-related facilities. For that purpose, a 10 m long sediment core was drilled in the area of the ancient open harbour immediately in front of the supposed ship sheds. It was studied with the tools of micropalaeontology, geophysics, sedimentology and geochemistry. To improve the reconstruction of the palaeoenvironmental conditions, reference samples of modern environments of the area were analysed. As indicated by marine ostracod and foraminifer taxa, the sediment core shows (from bottom to top) that the initially fully marine conditions changed to a more restricted fauna indicative for a more sheltered bay with brackish waters. This layer dates to Hellenistic times. It can, however, be shown that the siltation process had produced a lagoon system already several hundred years BC. The Elaia embayment was first used as a natural harbour. It was equipped with breakwaters in the Hellenistic period. The progressive siltation caused the abandonment of the harbour in Late Roman Times. Highlights: Microfossil (Foraminifera and Ostracoda) analyses of Hellenistic and Roman harbours. Palaeoenvironmental studies on the Aegean coast of Turkey. Elaia – the maritime satellite of Pergamum. Multidisciplinary approach to detect Hellenistic ship sheds.